UJI AKTIVITAS ANTIBAKTERI EKSTRAK DAUN SAMBILOTO (Andrographis paniculata Nees.) TERHADAP Staphylococcus aureus - Dzulasfi Dzulasfi (Akademi Farmasi Yamasi Makassar, 2022)
This study aims to determine the antibacterial activity of bitter leaf extract (Andrographis paniculata Nees.) against staphylococcus aureus. This research was conducted experimentally in the laboratory, the extract was made by maceration method using 96% ethanol. Concentration of 2%, 3%, positive control, and negative control were made. Based on the results of research that has been carried out that the ethanol extract of sambiloto leaves at a concentration of 2% does not occur / there is an inhibition zone, at a concentration of 3% has an inhibition zone of 8,5 mm, the positive control has an inhibition zone of 12.33 mm, and the negative control does not occur / there is an obstacle zone